Análisis integral y propuesta de mejora para una consultora de selección de personal - Calagua Mojorovich, Ivo Sebastian (2020)
The current project evaluates a HR medium company in an integral manner, whose core business is to deliver recruitment and selection services in the Peruvian market. The main problem is reflected in estimated delivery time, and service level, whereby deviate from the communicated plan to client. It had as a result a low rating in the customer satisfaction survey. These time delays and reprocessing are because of in the absence of planning of leaders in each Department, training workshops, in addition, lack of IT systems that hamper tracking accurate projects. In this situation, in order to apply for a continuous improvement inside company, it proposes implement Quality Management System based on ISO 9001:2015 Standard, which make laboral awareness of continuous improvement and apply policies, procedures, and instructional methods that regularize and standardize processes. Henceforth, the aim of this current dissertation is to elevate key principal indicators, based on economic, finance, commercial and strategic diagnosis. Thus, supporting values within range, and seek to reduce costs and to elevate sales level. In addition, the indicators were therefore designed more to get accurate solutions, justifying its technical, social, and economic viability, to discern the best option solution. Finally, it verified the hypothesis mentioned at introduction chapter: the integral improvement in the evaluated company will allow to improve the technical and economic performance indicators, as well as the optimal development of the main processes.